Recurrence Patterns in the k-mino game - Morales, César Andrés (2019)
In this work we study two generalizations to the double-6 domino tiles. In a general way, it is considered the k-minó, P(k, n), which consists in combining the numbers from 0 to n in groups of k. With this approach and using a new procedure it is found interesting recurrence patterns in function of the k and n parameters in order to obtain the number of pieces and the sum of the score of all pieces of the mentioned game. In a sequential way it is studied the domino P(2, n) and the trimino P(3, n) in order to generalize to P(k, n). The obtained results are related with the Pascal’s triangle and another mathematical topics as combinatorial, numerical sequences and series of higher-order, symmetric matrices, symmetric tensors, and complete graphs.